Translating the African postcolony:the conflict of selves, Intercultural dialogue and the location of the translator in the German translation of things fall apart and arrow of God (2012)
The translation of African postcolonial literatures into Western languages bespeaks the cultural encounter and intercultural relations of asymmetry that subsists at the dialogic and discursive spheres in the African postcolony between "ex-colonized" African cultures and societies and "excolonizer" Western cultures and societies. It also mirrors the location-in-conflict of the translator, especially the Western translator, of African postcolonial literatures, who deliberately or not, willingly or unwillingly, consciously or subconsciously mediates the conflict of cultural identities. This paper illustrates this in-between location-in-conflict of the Western translator of postcolonial African literatures in the German translation of Chinua Achebe's Things Fall Apart and Arrow of God and points to the critical position of the translator of African postcolonial texts in the dialogue between cultures in asymmetrical relations and, consequently, the ethical demand on the him/her to provide adequate and true representation of the identity of African source cultures in order to promote a progressive dialogue between cultures.